Geographical Analysis of Suicide Cases in Maysan Governorate from 2005 to 2023 - Hussien , Mahdi Nasser (Thi Qar Arts Journal, 2024)
Suicide, in its comprehensive sense, refers to the deliberate act that ends with a person killing themselves. It is a new phenomenon in Iraqi society, which is characterized by customs and traditions that prohibit such actions. This phenomenon has a significant impact on people’s minds as it has been growing in all Iraqi governorates, particularly in Maysan Governorate. The number of suicide cases recorded in the governorate from 2005 to 2023 is approximately 255 cases. The study indicated that there are many factors and motives for suicide that intersect, including social, economic, and psychological factors, and it is impossible to separate them and identify the main reason that was adopted as a motive for suicide. To reduce this phenomenon, efforts must be combined to provide meaningful job opportunities for the population in the governorate, especially for the youth, and to develop plans to prevent drug, sedative, and alcohol abuse.